A non-constructive proof of the existence of stable matchings in the marriage game - Cesco, Juan Carlos (2011)
In this note we present a non-constructive proof of the existence of stable matchings in the marriage model which uses a game theoretic approach. To this end, we develop a theory of hedonic partitioning games. Our approach differs from that used by Sotomayor (1996) based upon fixed point theory.